Prevalence of Carpal Tunnel Syndrome and De-Quervain Tenosynovitis among PUBG Players - Gul, Maham; Rauf, Hassan; Khan, Fatima (Surabaya Physical Medicine and Rehabilitation Journal, 2025)
Background: Portability and access to the internet are now the norm for everyone from school children to corporate business individuals allowing the playing of online games like Player Unknown’s Battlegrounds (PUBG) and other gaming. As for e-sports, there are some cognitive gains while game addiction especially among young people is on the rise. Excessive playing of games can cause musculoskeletal problems like strained neck muscles, and illnesses such as carpal tunnel syndrome, and de Quervain’s tenosynovitis. Aim(s): This cross-sectional study sought to estimate the percentage prevalence of CTS and DQT in PUBG players and their addiction level to gaming. Material and methods: The sample comprised 382 students with demographic data obtained using questionnaires completed independently by the participants. Gaming addiction was measured with a 21-item addiction scale while CTS was measured with the Boston Carpal Tunnel questionnaire; and DQT with the Finkelstein test. Result: Thus, 42.1% of PUBG players were identified as players with GA. The calculated frequency for de Quervain’s tenosynovitis was 52.9% the mean symptom severity of patients was 17.53±6.00 and the functional status of patients was 11.19±4.41 showing mild pain and limitation to the function. However, the level of carpal tunnel syndrome was relatively low in the participants of the present study. Conclusions: In this PUBG participants’ study, 52.9% had de Quervain’s tenosynovitis, largely with mild to moderate pain. However carpal tunnel syndrome was comparatively low in this instance. These findings indicate that musculoskeletal health is adversely affected by gaming and mostly the upper extremities are affected. Keywords: Carpal tunnel syndrome, De Quervain’s tenosynovitis, PUBG, Gaming Addiction, Musculoskeletal disease